Analisis Pengaruh Pengetahuan Investasi, Modal Minimal, dan Persepsi Risiko terhadap Minat Berinvestasi di Pasar Modal di Desa Bulu Kecamatan Bancar - A’yun, Inarotul; Zakiyah, Rochatud; Istiqomah, Widya (Journal of Industrial and Syariah Economics, 2024)
This research aims to analyze the influence of investment knowledge, minimum investment capital, and risk perception on interest in investing in the capital market among the people of Bulu Village, Bancar District. Using the multiple linear regression method, this research found that these three variables did not have a significant effect on investment interest. These results show the need for a more holistic approach to increasing investment interest among the public, including more comprehensive counseling and education. It is hoped that this research can contribute to the development of more effective and relevant investment policies, as well as increase public awareness about the importance of investing. By increasing knowledge and understanding about investment, the people of Bulu Village are expected to be able to take advantage of existing investment opportunities to improve their standard of living and welfare. Apart from that, it is also hoped that the results of this research will become a reference for related parties in designing more effective education and outreach programs so that they can encourage community participation in the capital market and contribute to local economic growth.